Seedling survival of three endemic and threatened Mexican cacti under induced climate change. Issue 1 (19th January 2016) - Aragón‐Gastélum, José Luis; Badano, Ernesto; Yáñez‐Espinosa, Laura; Ramírez‐Tobías, Hugo M.; Rodas‐Ortiz, Juan Pablo; González‐Salvatierra, Claudia; Flores, Joel
Abstract: Human‐induced warming may increase the risk of local extinction for plant species with low tolerance of elevated temperatures. The Chihuahuan desert harbors the highest diversity of globose cacti in the world and most of them are at risk of extinction. Predictive models of climate change indicate an increase in summer temperature of 1–2°C by 2030 for this desert. Nevertheless, studies on the vulnerability of cacti species in early development phases to future climate change are scarce. We assessed the survival of three threatened cacti species from the Chihuahuan desert under induced warming. Open‐top chambers (OTCs) were used to simulate the effect of global warming on 2‐year seedlings of E chinocactus platyacanthus f. visnaga, F erocactus histrix and S tenocactus coptonogonus . OTCs had higher temperature and lower humidity than control plots, and these elevated temperatures reduced seedling survival. Within the OTCs, no living individuals of any species were found after 105 days. Conversely, in the control plots, the three cacti species showed variable numbers of survivors after this period. Therefore the predicted global warming scenarios will greatly limit plant recruitment and the long‐term persistence of natural populations of Mexican endemic cacti species. Abstract : We assessed the survival of three threatened cacti species from the Chihuahuan desert under induced warming. After warming, no living individuals of any species were found after 105 days; conversely, in the control plots, the three cacti species showed variable numbers of survivors after this period. Therefore, predicted global warming scenarios will greatly limit plant recruitment and the long‐term persistence of natural populations of Mexican endemic cacti species.